PUSAT INTEGRASI AGRIKULTUR DI BUMI SERPONG DAMAI - Yunior Dharma Aryindra; Petrus Rudi Kasimun (Jurusan Arsitektur dan Perencanaan, 2019)
The government has the idea to develop a Modern Agricultural Zone in BSD (Bumi Serpong Damai) covering an area of 36ha which can support for 700ha of agricultural land around the area. We need a place where producers, consumers and the public can gather together to explore, develop and share experiences in the food production system in urban area. This will be great first movement for the next greater movement so that agriculture can merge into city-life and become a daily life for the urban community. Agricultural Hub in BSD has potentiallity to reduce barriers between consumers and producers which usually take long times cyclus because production activies are carried in the villages and sales in urban areas, but with this Agricultral Hub we can break the long chain so it can create a sustainable and efficient cyclus. Because this building located in the middle of the city, it provides direct education for the urban community about agriculture and the renewal and development of agricultural technologies. Agricultural Hub in Bumi Serpong Damai operates with a number of main programs whose serving and providing all cyclus of the food production process to reach consumers. Starting from production, process, cooking to sales available in here, plus there are research facilities and offices for young start-ups who want to enter the world of agriculture. Located in the CBD (Central Business District) of BSD and directly adjacent to agricultural land makes Agricultural Hub in Bumi Serpong Damai a connector between urban areas and agricultural land, which make benefit to the areas. AbstrakPemerintah memiliki gagasan untuk mengembangkan Kawasan Pertanian Modern di BSD (Bumi Serpong Damai) seluas 36 Ha yang dapat memberikan dukungan terhadap lahan pertanian seluas 700 Ha di sekitar kawasan tersebut. Oleh karena itu, dibutuhkan wadah produsen kota. Pusat Integrasi Agrikultur memiliki potensi dirancang untuk mengurangi hambatan antara konsumen dan produsen yang biasanya berlangsung secara berjenjang dan panjang namun dengan adanya pusat ini dapat memutuskan rantai tersebut sehingga dapat menciptakan iklim yang berkelanjutan dan efisien. Serta dengan letaknya yang berada di tengah kota memberikan edukasi secara langsung bagi masyarakat kota mengenai apa itu pertanian serta pembaharuan dan pengembangan teknologi-teknologi pertanian. Pusat Integrasi Agrikultur di Bumi Serpong Damai beroperasi dengan beberapa program utama yang sifatnya melayani dan menyediakan semua tahapan proses produksi pangan hingga sampai ke tangan konsumen. Dimulai dari produksi, proses, memasak hingga penjualan tersedia disini ditambah dengan adanya fasilitas riset dan kantor bagi start-up muda yang ingin masuk ke dalam dunia agrikultur juga tersedia di sini. Dengan lokasi yang berada di kawasan CBD (Central Business District) BSD serta berbatasan langsung dengan lahan pertanian menjadikan Pusat Integrasi Agrikultur sebagai konektor antara kawasan perkotaan dan lahan pertanian, yang tidak memutus tetapi menyambungkan antar keduanya.